ORF, an operational framework to measure resilience in social–ecological systems: the forest case study - Francisco Lloret; Pilar Hurtado; Josep Maria Espelta; Luciana Jaime; Laura Nikinmaa; Marcus Lindner; Jordi Martínez-Vilalta (Sustainability Science, 2024)
Resilience is commonly addressed when dealing with the sustainable planning and management of social–ecological systems, but we lack a unified framework for its quantitative assessment and application. We present an operational resilience framework (ORF) based on recognizing and relating several elements: system variables (e.g., ecosystem services), disturbances and stressors acting at given spatiotemporal scales, a reference state, and metrics comparing the observed system variables to the reference state. These elements fit into a rationale aimed at identifying resilience predictors suitable to be managed and co-drivers which describe non-manageable context, reflecting the mechanisms involved in resilience. By a systematic search of the presence of the ORF concepts in 453 empirical studies assessing resilience, we corroborate that ORF can be applied to studies on forest social–ecological systems. This literature survey shows that ORF elements are commonly recognized, although the logical narrative relating them is not always explicit, particularly in socioeconomic-focused studies. We advocate that the proposed ORF allows to standardize the terminology and to frame and measure resilience, allowing sounder comparisons and better-supported recommendations for the improvement of resilience in social–ecological systems, particularly in forest systems.